IPad in education for dummies - Gliksman, Sam (Laura Ann); 1906-1998.; 1970- (Hoboken, NJ John Wiley, 2014)
For kids, the iPad is a canvas--and given the freedom to explore and express themselves, students can be wonderfully creative and imaginative with technology. This handy guide serves as a roadmap for the iPad's use as an educational tool, giving you everything you need to deploy this ultra-cool device across all curricula and grade levels.
Includes index.
Keywords: Mobile communication systems in education -- Handbooks, manuals, etc; iPad (Computer) -- Handbooks, manuals, etc; iPad (Computer); Educational technology